2020
DOI: 10.1111/php.13342
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Formation by Near‐infrared Radiation in Rabbits

Abstract: Surveys and epidemiological studies have shown an increased prevalence of cataracts in workers in the glass and steel industries. These cataracts are associated with exposure to intense infrared radiation (IR) emitted from heated materials and industrial furnaces. Thermal model calculations predicted that near and far IR would cause cataract with different mechanisms. The present study investigated cataract formation by near IR. Eyes of pigmented rabbits were exposed to IR at a wavelength of 808 nm. Morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
8
1
1
Order By: Relevance
“…One possible explanation for this difference is that the IR-exposed area of the eye was small in his study compared with the present study (3 mm vs. 5 mm in diameter), allowing less radiant power (9/25 or 36%) to enter the eye for the same irradiance. However, in our present and previous studies, well-defined lens opacification of uniform density was observed under the part of the iris exposed to an IR beam with a top-hat intensity distribution (13), suggesting that the threshold irradiance is independent of the size of the exposed area. Thus, it is necessary to investigate if the threshold irradiance varies with the exposed-area size.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…One possible explanation for this difference is that the IR-exposed area of the eye was small in his study compared with the present study (3 mm vs. 5 mm in diameter), allowing less radiant power (9/25 or 36%) to enter the eye for the same irradiance. However, in our present and previous studies, well-defined lens opacification of uniform density was observed under the part of the iris exposed to an IR beam with a top-hat intensity distribution (13), suggesting that the threshold irradiance is independent of the size of the exposed area. Thus, it is necessary to investigate if the threshold irradiance varies with the exposed-area size.…”
Section: Discussioncontrasting
confidence: 64%
“…Thus, it may be necessary to lower the exposure limit for exposure durations shorter than 4 s. The finding that the threshold radiant exposure increases with increasing exposure duration (Fig. 3) adds to the evidence that 808 nm IR causes acute lens opacification by a thermal mechanism (13). In a thermal damage mechanism, as exposure duration increases, higher radiant exposure is required to achieve sufficiently high temperature to cause damage in the target tissue because heat is conducted away from it during the exposure (19).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations